Cattle weight and other body measurements within Son La province of Vietnam - Marshall, Karen; Malinga, Sophie; Poole, Elizabeth; Dung, Le Tien; Tuan, Han Anh; Duc, Do Van; Dai, Nguyen Van; Le Thi Thanh, Huyen (2025)
The dataset includes both household-level and animal-level characteristics. At the household level, data collected included geographic information such as the name of the commune, household number, and the number of eligible animals. Background information about the farmer was also captured.